Voice onset time of plosive consonants in initial position in badidni dialect - Kamel, Warhel; Salih, Salwa; Bijan Khan, Mahmoud (Humanities Journal of University of Zakho, 2023)
Phoneticians have presented several ways and theories for knowing the features and characteristics of plosive consonants. Acoustic ways are ones that languages’ plosive consonants are determined by them. In the last 60 years VOT was widely used as an acoustic parameter by phoneticians for comparing voicing contrast and determining the categories and features of plosive consonants as an acceptable way. Until now it’s not known that plosive consonants are determined in badini dialect according to the VOT parameter. This study is an attempt to what extent we can benefit from the mentioned parameter for specifying voicing contrast distinction, voicing categories and their properties and features. For this purpose the two plosive consonants /b, p/ are used as a stimulus of this investigation in the initial 6 monosyllabic words in the environment of the two vowels /ɑ æ,/. The collected data are taken from (20) badini dialect speakers. It’s assumed that voicing contrast, VOT values and the categories of plosive (voiced and voiceless) consonants are different in baddini dialect. Depending on procedures and statistical analysis tests it concludes that; VOT is formed in three ways and three separate values. This study consists of five sections; the first section is the introduction, the second one is theoretical framework, in the third section the procedures of doing this study are shown, statistical results and discussing them are mentioned in the fourth section and the conclusions of the study are shown in the fifth section.